Assessing a ban on the use of UV tanning devices among adolescents in Ontario, Canada: first-year results - Nadalin, Victoria (Can J Public Health, 2018)
OBJECTIVES: To describe the effect of the first year of a ban on UV tanning device (beds, lamps) use among those under 18 years of age in Ontario, Canada. METHODS: Online questionnaires were completed by adolescents in grades 7 to 12, aged less than 18 years: one when the ban was enacted (May 2014) and a second a year later (May 2015). Questionnaires asked grade, age, sex, and about use of UV tanning devices in the previous year. Recent users were asked about length, frequency, and location of use; service refusals and reasons; awareness of signs/warning labels; and use of eye protection. Weighted estimates and confidence intervals were generated. RESULTS: There were 1561 participants in 2014 and 2305 in 2015. No reduction was observed in UV tanning device use (6.9% vs. 7.9%) in the 12 months preceding the survey. In 2015, most respondents used UV tanning devices in beauty establishments, which was a shift away from gyms and fitness centres as seen in 2014. Non-significant increases occurred in the proportions noticing warning signs/labels (57% vs. 71%), required to wear eye protection (92% vs. 99%), and refused service (17% vs. 21%). Most adolescents who were refused service did not use tanning devices that year (72%). CONCLUSION: Use did not change in the year following enactment of a ban on UV tanning devices among youth in Ontario. The ban did lead to improvements in service refusal, awareness of warning signage, and use of eye protection. As service refusal deterred future use, enhanced enforcement is important.